Benevolent Situations and Gratitude. Issue 4 (2nd October 2021) - Telech, Daniel
ABSTRACT: This commentary explores a question concerning the positive reactive attitudes that is raised by Kwong-loi Shun's intriguing remarks on gratitude. Shun's overarching aim in 'Anger, Compassion, and the Distinction between First and Third Person' is to outline and motivate a Confucian, situation-focused, account of our evaluative responses, one according to which the commonly drawn distinction between first- and third- personal attitudinal perspectives is undermined. While Shun does not settle on an answer to the question, 'can gratitude be (fittingly) felt toward agents who benefit third-parties (with whom one is not specially related)?', he suggests a positive answer. Intrigued by this idea, I consider how the resources of Shun's situation-based view might accommodate gratitude of this sort. Two opposed routes present themselves. On the first (expansive) approach, expressions of grateful reciprocation are extended to persons who presently receive only our approval or approbation. On the second (restrictive) approach, gratitude in effect collapses into approval, and our interpersonal practices are rid not only of angry payback, but also of the positive payback presently associated with gratitude.